If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6m + -2y = 3y + -2 Reorder the terms: 6m + -2y = -2 + 3y Solving 6m + -2y = -2 + 3y Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '2y' to each side of the equation. 6m + -2y + 2y = -2 + 3y + 2y Combine like terms: -2y + 2y = 0 6m + 0 = -2 + 3y + 2y 6m = -2 + 3y + 2y Combine like terms: 3y + 2y = 5y 6m = -2 + 5y Divide each side by '6'. m = -0.3333333333 + 0.8333333333y Simplifying m = -0.3333333333 + 0.8333333333y
| 2+3(-6+4)=8 | | n+10-6=7 | | 4(v+4)-7v=-14 | | M-7m-9m+2= | | y=-5x+16 | | -h-24=5-h | | 10t-5t^2=2 | | 21-2(3)= | | 0.3-0.625=0.875 | | 2x+1y=36 | | 6x^2+90x+324=0 | | 3y+2-2y-5=-4y-3 | | 16b=40-4b | | 3y+2-2y-5=-4x-3 | | e=mc(2) | | -7(6-x)-5x=-24+5x | | 10x-6=10+6x | | 0.16(12)+0.04x=0.08(24+x) | | 3y+2-2y-5=-2x-2 | | (2x+1)+(4-3x)=10 | | 7z-10-z+4=0 | | x+2*x+2*x+2*x+2+11=49 | | x+1/3-x+2/4=x+1 | | 7x+5-2x+1=4x+8 | | 9x^4-16x^2=0 | | 6-4v+4=v+5 | | 0=2(2x^3+3x^2+7x-5) | | 14x+140=147+13 | | 3t+21= | | x^2+19x-216=0 | | 2x+2(x-20)=212 | | n^4-9n^2=0 |